Pregnancy outcome in patients presented with Peripartum Cardiomyopathy: A five-year study in a tertiary care centre - Adhikari, Lipika; Sarkar, Sandip (Asian Journal of Medical Sciences, 2022)
Background: Peripartum cardiomyopathy is a relatively rare type of dilated cardiomyopathy that presents in late pregnancy or the early postpartum period. Although the condition is prevalent worldwide, women with black genealogy seem to have greater risk. Possible other risk factors are elderly maternal age, hypertension, multiparity, multifetal pregnancy etc. Although the pathophysiology of peripartum cardiomyopathy is still obscure, recent studies suggests the important role of vasculo-hormonal pathway along with several other possible factors e.g. myocarditis, abnormal immune response to pregnancy, abnormal response to increased hemodynamic burden, malnutrition, inflammation and apoptosis . Aims and Objectives: To find out the prevalence, risk factors and pregnancy outcome of peripartum cardiomyopathy (PPCM) Materials and Methods: Sixty-eight patients of PPCM admitted in G&O department of RG KAR Medical college were taken. Clinical evaluations, Hematological evaluation, biochemical study, ECG and Echocardiography were done. Patient outcome was also compared between two groups of patients having Left Ventricular ejection fraction less than 35% and more than 35%. Result: Prevalence of PPCM was 0.09%, maternal mortality was 87 per 1000 live births and perinatal mortality was 43 per 1000 live births. Patients with lower ejection fraction showed poorer outcome. Conclusion: Patients with higher NYHA functional class, lower ejection fraction and larger left ventricular cavity showed worse maternal and perinatal outcome.